THE INFLUENCE OF HEALTH PROTOCOLS (CHSE) ON TOURISTS’ MOTIVATION TOWARD VISITING DECISION IN FLOATING MARKET LEMBANG - Susilo, Adzmi Fillah Dianariesla Garianjani; Beta Budisetyorini; Wisnu Rahtomo (International Journal of Sustainable Competitiveness on Tourism, 2022)
Ten days after the President of Indonesia announced the first COVID-19 case, WHO declared that COVID-19 is a global pandemic. Since then, the virus has spread rapidly and caused numerous deaths and terrible economic impacts. According to UNWTO, tourism is one of the most effective sectors, due to worldwide restrictions on travel and closed borders. In Indonesia alone, the pandemic decreases around Rp 85 trillion of Indonesia’s tourism revenue by 2020. Based on many reports a lot of hotel and food businesses were shut down and many workers were impacted. In an attempt to recover the condition Ministry of Tourism and Creative Economy implemented a program called CHSE certification to ensure tourists' safe travel. Floating Market Lembang is one of the certified CHSE destinations in Bandung. The subject of this study is the visitors of Floating Market Lembang, who visited the destination around December 2020 to June 2021. This study aimed to see the impact of CHSE certification in Floating Market Lembang on tourists’ visiting decisions. As destination attributes play a big role in tourists’ visiting decisions, this will be seen through tourist motivation, push and pull factors. Quantitative methods used to generate tourists’ opinions on the matter then will be analyzed using regression analysis. The result of this study shows that push factors alone have no influence on tourists’ motivation, pull factors, on the other hand, have an influence on tourist’s motivation. At the same time, both push and pull factors have an influence to visit Floating Marker Lembang under CHSE circumstances.